Multi-objective models for crop rotation planning problems - Pontes, Roberto Da Silva Gervasio; Brandão, Diego Nunes; Usberti, Fábio Luiz; De Assis, Laura Silva (Agricultural systems, 2024)
Agriculture is a vital component of the global economy and modern societies. It has undergone significant consolidation and transformation in response to the food supply crisis, highlighting the important relationship between humans and the environment. However, concerns remain about food security, particularly with the projected population growth of over 9.5 billion by 2050. The computerization of agri-food supply chains has emerged as a significant response to these challenges. (1) Develop a multi-objective model that explores both net return and crop diversity. (2) Solve the problem using techniques that guarantee optimality. (3) Evaluate the gain in crop diversity versus the net return of the optimized configuration. The study presents four Multi-objective Mixed-Integer Linear Programming models with integer and binary decision variables for Crop Rotation Planning Problems. The objectives are to maximize net income and increase crop diversity and land utilization. The study exclusively employs linear programming techniques to solve the models resulting in an optimal solution. A comparative analysis with existing models in the literature, which primarily focused on maximizing net income, yielded a noteworthy result. The proposed models demonstrate an average increase of 60% in crop diversity, with net return losses of less than 5%. In conclusion, this research provides valuable information for crop rotation planning and highlights the importance of agricultural farm management and precision agriculture in addressing current challenges. The innovative nature of this research is exemplified by the use of mixed-integer linear programming techniques to solve a multi-objective problem with integer and binary variables. The obtained results demonstrate increased crop diversity and minimal economic losses, which have significant implications for several areas of agricultural science, policy, and practice. [Display omitted] •Proposing a multi-objective model for crop rotation planning problem using mixed-integer linear programming.•A new objective function encompasses both net income, land use, and crop diversity.•Environmental, Social, and Governance (ESG) and sustainability aspects are considered in the decision process.•Multi-objective mixed-integer linear programming with the weighted sum method is used to achieve optimality.•With less than a 5% reduction in net income, a 60% increase in crop diversity has been achieved.